Regional Stability Analysis of Red Clay Slope Based on Different Failure Modes: A Case Study in Taizaifu Area, Fukuoka - Fang Wei (Advances in Civil Engineering)
Red clay slopes have different failure modes in different geological and climatic contexts. Underlying weak layers are frequently witnessed in integral failures because of the reverse consolidation characteristics. On the contrary, heavy rainfall often causes superficial sliding for a considerable infiltration through developed microfractures. Based on the Geographic Information System, regional stability of red clay slopes was evaluated with two failure modes, such as “integral sliding” and “planar sliding.” First, terrain and borehole data of the study area were used to construct the digital elevation model. Second, slope units were partitioned as research objects. For integral sliding, the slip surface was supposed to lie above the strata interface, and it was regarded as a lower part of an ellipsoid. After calculating safety factors of potential slip surfaces that were randomly generated by the Monte Carlo method, the minimum safety factor of the slope unit and the critical slip surface could be determined. For shallow landslides triggered by rainfall infiltration, the one-dimensional infiltration model and infinite slope model were used. Moreover, the difference between the sliding direction of each column and the main aspect of entire slope unit was considered in safety factor calculation. Finally, regional slope stability characterized by the safety factor would be available; thus, it would be beneficial to sliding prevention and disaster treatment in this region.